The Use of Loose-Part to Improve Early Childhood Self-Sufficiency - Ika Budi Maryatun; Martha Christianti; Eka Sapti Cahya Ningrum; Nur Cholimah; Luluk Nur Aisyah; Aliyah Latifah Hanum (Yayasan Keluarga Guru Mandiri, 2024)
This research aims to increase independence by using loose parts. The research subjects were children aged 4-5 years, totaling 16 children. The research procedure includes planning, implementation of action, observation, and reflection of each cycle-given action in five meetings. This improvement data was collected using observation techniques and analyzed descriptively, quantitatively and qualitatively. The results show that loose play can increase the independence of children aged 4-5 years. These results are indicated by an increase in the percentage of independence in action from pre-cycle to cycle 1 by 20.84%, then from cycle 1 to cycle 2 increased by 30.73%, and the average percentage of children's independence in cycle 2 was 84.38%. The results of this study can be used as a reference by kindergarten teachers in improving classroom learning related to children's self-sufficiency.